On a Mission to Break Ground for a More Democratic School System - Grevle, Tessa Eriksen (Nordic Journal of Comparative and International Education (NJCIE), 2023)
The importance of building democratic competency in the face of current global challenges cascades down into national curricula. Illustratively, in 2020, Norway introduced a new national curriculum that conveyed an expectation that students should experience a democratic school society in practice. In response to this new curriculum, in 2019, an upper secondary school in Norway decided to embark on a mission to develop and implement a new pedagogical model. The ambition was to increase the students’ sense of codetermination and participation in school, the local community, and society at large. Subsequently, an interdisciplinary pedagogical model has been in development at the school, in which the subject content is organized according to overarching topics. These topics are presented to students as quests called learning missions. Through in-depth interviews with teachers and leaders currently working on developing the new pedagogical method at the school, the current article investigates the challenges and opportunities the participants encountered in this process. The data have been coded through a stepwise deductive-induction method and analyzed using Bernstein’s concepts of classification and frame. The participants identified the inflexible organizational structures of the school—such as the school administrative system, the building, assessments, and the set timetable—as aspects that made it challenging for the school to depart from the dissemination-based approach to education. Inversely, the implementation of interdisciplinary topics in the Norwegian National Curriculum is one example of a structural change that the participants thought had opened up more flexibility. However, the participants experienced that this flexibility was not extended into the regulations controlling how time is spent in school or the assessment forms. Hence the article concludes that structural changes are necessary to enable the growth of pedagogical models that can increase students’ codetermination, active participation, and real-life experiences in schools.